Why go public? Public configurations and the supportive and divergent views towards public district heating in the Netherlands - Herreras Martinez, Sara; Harmsen, Robert; Menkveld, Marijke; Kramer, Gert Jan; Faaij, André (Frontiers in Sustainable Cities, 2023)
Introduction Cities are taking up services of social importance under the (re)municipalisation movement. The Dutch government embarked on an ambitious heat transition and proposed in 2022 to make all district heating projects public or semi-public, with a majority public share. This proposal has sparked intense debates among groups in favour of and against a shift to public ownership. Methods This study assessed 16 public projects through qualitative research and uncovered the arguments for and against public ownership among key public and private stakeholders. Results While public ownership is deemed necessary to meet social objectives and address the shortcomings of private models, critical views question the economic performance and inappropriate political choices in some public projects. These critical views propose alternative ways to safeguard public values, such as ensuring affordability and meeting climate goals. Despite disagreements, public and private actors recognise the shared responsibility and the importance of the other's role. They agree that the central government's proposed mandate for public ownership may limit flexibility at the local level and prevent other effective configurations like public-private partnerships with equal public-private shares. Discussion Reflecting on the study findings, it is debatable whether mandating public ownership nationwide, as proposed by the Dutch government, should become the approach to tackle current challenges instead of allowing more flexibility. The upcoming Heat Act may reduce key issues justifying public ownership, such as affordability, cherry-picking and the lack of transparency of private projects. Further research is needed to determine whether public ownership would enhance citizens' support and speed up realisation. Public ownership may still be necessary if social and cost benefits outweigh those from other configurations or long-term concession contracts are too risky. Implementing regulations protecting public values and enabling the coexistence of public, private or public-private configurations tailored to each unique local context could be an alternative, as successful district heating sectors abroad demonstrate.